Symptoms in different severity degrees of bruxism: a cross-sectional study - Cinthia Santos Miotto Amorim; Glauco Fioranelli Vieira; Eliete Ferreira Osses Firsoff; Jecilene Rosana Costa Frutuoso; Elizabeth Puliti; Amélia Pasqual Marques (Universidade de São Paulo, 2016)
ABSTRACT Objective: The aim of the present study was to evaluate symptoms of the muscle pain, sleep quality, oral health, anxiety, stress and depression in individuals with different severity degrees of bruxism. Methods: Seventy-two individuals with bruxism were enrolled in the study, classified into: moderate (n=25) and severe (n=47) bruxism. Pain intensity was assessed using the Visual Analogical Scale, pain threshold with algometer, sleep quality by the Pittsburgh Sleep Quality Index, oral health by the Oral Health Impact Profile, anxiety by the State-Trait Anxiety Inventory, stress by the Perceived Stress Scale and depression using the Beck Depression Inventory. The significance level considered was 5%. Results: The results showed that individuals with severe bruxism presented greater muscle pain intensity, sleep disorder, worse oral health, high anxiety level and dysphoria with statistically significant differences (p<0.05) than individuals with moderate bruxism, except in pain threshold and stress (p<0.05). Conclusion: Data suggest that individuals with severe bruxism have more intense symptoms. They present greater muscle pain, alterations in sleep quality and oral health, anxiety and depression than individuals with moderate bruxism. However, both present similarity in stress.